2018
DOI: 10.2147/opth.s181256
|View full text |Cite
|
Sign up to set email alerts
|

Post-marketing surveillance study of the safety of dexamethasone intravitreal implant in patients with retinal vein occlusion or noninfectious posterior segment uveitis

Abstract: PurposeTo evaluate the long-term safety of dexamethasone intravitreal implant (DEX) in patients treated for macular edema associated with retinal vein occlusion (RVO) or noninfectious posterior segment uveitis (NIPSU) in clinical practice.Patients and methodsMulticenter (102 sites in France, Germany, Spain, UK), prospective, observational, post-authorization safety study in adult patients treated with DEX. Data collected up to 2 years after enrollment included serious adverse events (SAEs) and adverse events o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
2
16
3
Order By: Relevance
“…Combined therapy has the advantages of synergistic effect, improving visual acuity and prolonging injection intervals (Singer et al., 2012). Inflammation is also involved in the pathogenesis of macular edema after RVO and noninfectious posterior segment uveitis (NIPSU) (Tufail et al., 2018). Studies have shown that aqueous humor levels of proinflammatory cytokines are reduced after DEX treatment in patients with RVO (Rezar-Dreindl et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Combined therapy has the advantages of synergistic effect, improving visual acuity and prolonging injection intervals (Singer et al., 2012). Inflammation is also involved in the pathogenesis of macular edema after RVO and noninfectious posterior segment uveitis (NIPSU) (Tufail et al., 2018). Studies have shown that aqueous humor levels of proinflammatory cytokines are reduced after DEX treatment in patients with RVO (Rezar-Dreindl et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although approved for the treatment of the underlying intraocular inflammation, a survey among uveitis specialists identified uveitic CME as the preferred indication [ 12 , 13 ]. Ozurdex® [ 14 ] appears less prone to high intraocular pressure and cataract occurrence than Retisert®. Iluvien® is a non-bio-degradable, 0.19 mg fluocinolone acetonide implant lasting up to 36 months [ 15 ].…”
Section: Intravitreal Therapymentioning
confidence: 99%
“…23,35 The AEs that occurred (increased IOP and cataract) were expected with intraocular corticosteroid treatment, and the observed safety profile of DEX was consistent with that reported in previous studies of DEX treatment for DME 23,28,38 and other indications. 39,40 Typically the increases in IOP in DEX-treated eyes were managed with topical IOP-lowering medication, and after IOP control was achieved, patients received subsequent DEX injections as planned. Only 1 (0.7%) DEX-treated patient required trabeculectomy, consistent with findings from the global registration studies in which 2 (0.6%) DEX-treated patients required trabeculectomy.…”
mentioning
confidence: 99%